Studi Faktor Psikologi Sosial dan Eksternal dalam Memengaruhi Kepatuhan Wajib Pajak - Kusuma Dewi, Sayyidah Nurul; Wahyandono, Matheas Prihargo; Seran, Valeria Flora; Hatta Hambali, Atika Jauharia (E-Jurnal Akuntansi; Vol 32 No 10 (2022)DO - 10.24843/EJA.2022.v32.i10.p01, 2022)
Tax compliance plays a very important role in increasing state tax revenues. This study aims to determine the effect of national pride, trust in authority, and the Automatic Exchange of Information (AEoI) system on tax compliance. The study also raises one social psychological factor, namely patriotism as a moderating variable that strengthens the relationship between national pride and tax compliance. The research uses a survey method and the sample is taxpayers who have NPWP. The results of the study indicate that there is an influence of national pride and the AEOI system on taxpayer compliance. There is no significant effect of the variable trust in authority on taxpayer compliance. The moderating variable in the form of patriotism cannot strengthen the influence of national pride on taxpayer compliance. The study concludes that the taxpayers of this study have a high spirit of nationalism and knowledge of the AEOI system, but trust in the authorities is still low. Keywords: Tax Compliance; Nationalis Pride; Trust; AEoI System; Patriotism.